An Investigation into Technical Writing Difficulties, Causes and Solutions - Alaraj, Mamoon (Technium Social Sciences Journal, 2022)
This study aimed at deeply scrutinizing and identifying the technical writing difficulties Saudi university students face, figuring out what caused these difficulties and creating solutions to them. Two five-member focus groups of engineering students were deployed, and the brainstorming technique was used to create questionnaire items. The draft developed was given to three specialists to revise, edit and proofread. The second version of the survey involved eight quantitative and qualitative questions of three types (Likert scale, checkbox, and rating). This version was piloted on 25 undergraduates, amended consequently (See appendix A), created by Google Forms, and lastly circulated via WhatsApp groups. Fifty-three university students from different majors participated in it. The findings revealed that spelling, technical terminology and coherence were the most difficult areas in technical writing, writing practice deficiency, lack of terminology and lack of vocabulary were the main causes that stand behind technical writing difficulties and practicing writing a lot and developing habits of intensive and extensive reading were the most effective solutions that can help students overcome these difficulties. Based on the findings of the study, some interpretations were discussed, and some recommendations were made.